The User Experience in Efforts to Create a Digital Library during a Pandemic COVID-19: Systematic Literature Review - Asma Rakha Dinazzah; Indira Irawati (Record and Library Journal, 2022)
Background of the study: The digital library is one of the places where it is used to find information related to the services provided by the library during the COVID-19 pandemic. However, many users feel that they complain about the performance of the digital library, which is difficult for users to learn, and feel that they have not paid attention to what users want. Purpose: This research was conducted to see the development of digital library publications with the analysis of user experience (UX) and to see the impact of user experience (UX) on digital libraries before and during the pandemic. Method: This study uses the Systematic Literature Review (SLR) method by collecting literature related to the topics discussed and then making selections to produce an overview of research on User Experience in digital libraries from 2011 to 2021. Findings:  The results of this study note that users' experience in digital libraries is quite good in terms of user appearance and convenience, and ease of access. However, some users are not yet comfortable with the new form of digital library. Users want comprehensive improvements to make it easier for users to find information and take advantage of online services on digital library webs. Conclusion: It is expected that user experience or user experience in digital libraries at an agency or organization is important for reliable development. End users want high quality services So that when in the current Covid-19 pandemic situation we are better prepared and continue to improve the quality of digital libraries